2012
DOI: 10.1109/tcbb.2012.88
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of the Ribosome Flow Model

Abstract: Abstract-Gene translation is a central process in all living organisms. Developing a better understanding of this complex process may have ramifications to almost every biomedical discipline. Recently, Reuveni et al. proposed a new computational model of this process called the ribosome flow model (RFM). In this study, we show that the dynamical behavior of the RFM is relatively simple. There exists a unique equilibrium point e and every trajectory converges to e. Furthermore, convergence in monotone in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 57 publications
0
100
0
1
Order By: Relevance
“…It was already shown that this model admits a unique equilibrium point e ∈ Int(C), and that any trajectory emanating from a feasible initial condition converges to e [52].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was already shown that this model admits a unique equilibrium point e ∈ Int(C), and that any trajectory emanating from a feasible initial condition converges to e [52].…”
Section: Discussionmentioning
confidence: 92%
“…It was shown in [52] that the dynamical behavior of the RFM is relatively simple. Let Int(C) denote the interior of C, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in Margaliot & Tuller [20], the RFM (1.1) is an SCTS on the open unit cube Int(C). For example, since _ x 2 ¼ f 2 ðxÞ, with f 2 (x) ¼ l 1 x 1 (1 2 x 2 ) 2 l 2 x 2 (1 2 x 3 ), we have @f 2 =@x i ðxÞ = 0 only for i ¼ 1,2,3.…”
Section: Monotone Dynamical Systemsmentioning
confidence: 83%
“…In the study of Margaliot & Tuller [20], we showed that there exists a unique equilibrium point e [ IntðCÞ, where…”
Section: > > > > > > > = > > > > > > > ; ð1:1þmentioning
confidence: 99%
“…[15], [16], [17], [18], [19], [20], [21]). In this case, every ribosome that leaves the chain releases the produced protein, so R(t) is the protein production rate at time t.…”
Section: Examplementioning
confidence: 99%